Integrated Lipidomic and Transcriptomic Analysis Reveals Lipid Metabolism in Foxtail Millet (Setaria italica) - Zhang, Haiying; Wang, Junyou; Zhao, Jing; Sun, Changqing; Wang, Jin; Wang, Qian; Qu, Fei; Yun, Xiaodong; Feng, Zhiwei (Frontiers in Genetics, 2021)
Foxtail millet (Setaria italica) as the main traditional crop in China, is rich in many kinds of high quality fatty acids (FAs). In this study, Ultra-high performance liquid chromatography-time-of-flight-tandem mass spectrometer (UHPLC-Q-TOF-MS/MS) was used to determine the lipids of JG35 and JG39. A total of 2633 lipid molecules and 31 lipid subclasses were identified, mainly including thirteen kinds of glycerophospholipids (GP), eleven kinds of glycerolipids (GL), four kinds of sphingolipids (SP), two kinds of fatty acyls (FA) and one kind of sterol (ST). Among them JG35 had higher contents of diacylglycerols (DG) and ceramides (Cer), while triacylglycerols, phosphatidyl ethanolamine, phosphatidic acid, sterol, fatty acyls and pardiolipin (TG, PE, PA, ST, FA and CL)were higher in JG39. Meantime, the correlation analysis of lipidomics and transcriptomics was used to map the main differential lipid metabolism pathways of foxtail millet. The results shown that a differentially expressed genes (DEGs) of FATA/B for the synthesis of FA was highly expressed in JG35, and the related genes for the synthesis DG (ACCase, KAS, HAD, KCS, LACS and GAPT), TG (DGAT and PDAT) and CL (CLS) were highly expressed in JG39. The results of this study will provide a theoretical basis for the future study of lipidomics, improvement of lipid quality directionally and breeding of idiosyncratic quality varieties in foxtail millet.